QR Code-Based Monopoly: An Example of The Fun of Gamification in Learning at Elementary School - Mulyawati, Yuli; Destiana, Dita; Zen, Dendy Saeful; Sari, Lusti Indah (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2024)
Digital media innovation is a way to empower 21st-century critical thinking skills in elementary school students. One of the innovations that can be used is QR code-based Monopoly Gamification in learning. The purpose of this research is the development and testing of monopoly QR code-based media. This gamification research design uses the ADDIE model which consists of the stages of analysis (issue analysis), design (product design), development (development), implementation (implementation), and evaluation (assessment). This research involved media experts, linguists, and subject matter experts to provide judgments, and students as media users. The results of this study came in the form of monopoly QR code-based media that received validation of media suitability aspects based on ISO 9126 quality at 83.63%, linguistic aspects by linguists at 100%, and material aspects by subject matter experts at 96.36%. The QR code-based proprietary learning media received positive responses from 33 students with a percentage of 90.8% in the